2018
DOI: 10.1155/2018/7692839
|View full text |Cite|
|
Sign up to set email alerts
|

Organic, Gas, and Element Geochemistry of Hydrothermal Fluids of the Newly Discovered Extensive Hydrothermal Area in the Wallis and Futuna Region (SW Pacific)

Abstract: Two newly discovered hydrothermal vent fields of the Wallis and Futuna region, Kulo Lasi and Fatu Kapa, were sampled for fluid geochemistry. A great geochemical diversity was observed and assigned to the diversity of lithologies as well as the occurrence of various processes. Kulo Lasi fluids likely formed by interaction with fresh volcanic rocks, phase separation, and mixing with magmatic fluid. Conversely, the geochemistry of the Fatu Kapa fluids would be mostly due to water/felsic lavas reactions. In terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 134 publications
2
20
0
Order By: Relevance
“…Thus, variations in chlorinity, from 34% higher to 9% lower than that of the seawater, can be explained by a process of phase separation (Bischoff and Rosenbauer, 1987). An adiabatic decompression of supercritical seawater Pitzer, 1989, Foustoukos andSeyfried, 2007a) would cause it to separate, at about 320-350 bars and 415-420°C (Konn et al , 2018) into two phases having the NaCl percentages observed at Kulo Lasi.…”
Section: Evidence For Phase Separationmentioning
confidence: 97%
See 4 more Smart Citations
“…Thus, variations in chlorinity, from 34% higher to 9% lower than that of the seawater, can be explained by a process of phase separation (Bischoff and Rosenbauer, 1987). An adiabatic decompression of supercritical seawater Pitzer, 1989, Foustoukos andSeyfried, 2007a) would cause it to separate, at about 320-350 bars and 415-420°C (Konn et al , 2018) into two phases having the NaCl percentages observed at Kulo Lasi.…”
Section: Evidence For Phase Separationmentioning
confidence: 97%
“…The high temperature fluids (>300°C) from the Kulo Lasi (Table 3) have unusually high concentrations of Mg (24.6 to 34.9 mM) and SO 4 2-(6.2 to 12.0 mM). However, the low pH (2.24 to 3.32) and the high temperature (338-343°C) of these fluids indicate that significant mixing with cold seawater at subsurface or during sampling is rather unlikely (Konn et al , 2018). Mixing with cold seawater would not maintain the temperature of 343°C and the low pH while increasing the concentration of Mg from 0 to ~50% of the seawater concentration.…”
Section: Unusual Composition Of the Fluidmentioning
confidence: 98%
See 3 more Smart Citations